Reduction of CSF Artifacts on FLAIR Images by Using Adiabatic Inversion Pulses - Hajnal, Joseph V.; Oatridge, Angela; Herlihy, Amy H.; Bydder, Graeme M. (American Journal of Neuroradiology, 2001)
Summary: The purpose of this study was to investigate the possibility that some artifactual high signals produced in CSF with fluid-attenuated inversion-recovery MR sequences could be due to inhomogeneity in the amplitude of the initial inversion pulse, and that this problem could be reduced or eliminated by the use of adiabatic inversion pulses. Studies with four volunteers showed dependence of high CSF signals in the posterior fossa on radiofrequency pulse amplitudes and that these signals could be eliminated by the use of adiabatic inversion pulses. Two illustrative clinical cases are included.